PENERAPAN MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Larasati, Niken; Apriliana, Silfia Marca Atika; Sapitri, Indah Nur; Supriyadi, Supriyadi; Izzatika, Amrina (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
Education in elementary schools requires the implementation of school-based management to improve the quality and competence of teachers as educators in order to achieve satisfactory school accreditation. The purpose of this article is to discuss the application of School Based Management (SBM) in an effort to improve the quality of education in elementary schools. The author uses qualitative methods in the form of library research through observing literature from various books, articles, web browsing and system analysis. The research results show that SBM provides more autonomy to schools. Quality education includes satisfactory service for graduates and the community. In implementing SBM in elementary schools, there are several factors that need to be considered, such as considerations and implementation strategies. In conclusion, management plays an important role in improving the quality and relevance of education.